A novel two-step Fe–Au type spin-crossover behavior in a Hofmann-type coordination complex Fe(4-methylpyrimidine)2[Au(CN)2]2. Issue 35 (1st July 2020) - Kitase, Kosuke; Kitazawa, Takafumi
Abstract : A Hofmann-type two-step spin-crossover (SCO) complex with a pyrimidine derivative ligand was synthesized. Abstract : A Hofmann-type two-step spin-crossover (SCO) complex with a pyrimidine derivative ligand, Fe(4-methylpyrimidine)2 [Au(CN)2 ]2, was synthesized, and this complex shows a two-step SCO phenomenon in the intermediate state. Symmetry breaking also occurs in the intermediate state. These results reveal three spin states within the complex for high-spin (HS), HS0.5 LS0.5, and low-spin (LS).